Deepening water scarcity in breadbasket nations - Qinyu Deng; Tyler Sharretts; Tariq Ali; Yufei Zoe Ao; Davide Danilo Chiarelli; Betelhem Demeke; Landon Marston; Piyush Mehta; Mesfin Mekonnen; Maria Cristina Rulli; Marta Tuninetti; Wei Xie; et al. (Nature Communications)
Abstract Water is crucial for meeting sustainability targets, but its unsustainable use threatens human wellbeing and the environment. Past assessments of water scarcity (i.e., water demand in exceedance of availability) have often been spatially coarse and temporally limited, reducing their utility for targeting interventions. Here we perform a detailed monthly sub-basin assessment of the evolution of blue (i.e., surface and ground) water scarcity (years 1980-2015) for the world’s three most populous countries – China, India, and the USA. Disaggregating by specific crops and sectors, we find that blue water demand rose by 60% (China), 71% (India), and 27% (USA), dominated by irrigation for a few key crops (alfalfa, maize, rice, wheat). We also find that unsustainable demand during peak months of use has increased by 101% (China), 82% (India), and 49% (USA) and that 32% (China), 61% (India), and 27% (US) of sub-basins experience at least 4 months of scarcity. These findings demonstrate that rising water demands are disproportionately being met by water resources in already stressed regions and provide a basis for targeting potential solutions that better balance the water needs of humanity and nature.